Effects of the pulse treatment with PP333 on the floral formation, POD isozymes, and soluble proteins of cucumber decapitated seedlings - LI Feng-yu; LIANG Hai-man (浙江大学学报. 农业与生命科学版)
The effect of the pulse treatment with PP333 on the floral formation of cucumber decapitated seedlings was studied, and the changes of the electrophoresis pattern of POD isozymes and soluble proteins 24 hrs after the pulse treatment were analyzed. The results were shown as below: The optimized stages of pulse treatment with PP333 were the 2nd, 3rd and 8th days after the decapitation was taken, and the percentages of floral buds were 3.5, 3 and 4 folds of the control respectively. There existed different activities of POD isozymes between the PP333-pulse treatment and the control of the decapitated seedlings, but it was obviously different in the soluble proteins. We could find a new basic band (Rf0.032) with PP333 treatment taken on the 3rd day after the decapitation was taken.